Artificial Intelligence Methodologies for Data Management - Alfaro-Marchant, M; Quezada-Llanca, L; Ternero-Saavedra, R; Serey-Araneda, J; Vargas-Guzman, M; Fuertes-Sanchez, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This study analyses the main challenges, trends, technological approaches, and artificial intelligence methods developed by new researchers and professionals in the field of machine learning, with an emphasis on the most outstanding and relevant works to date. This literature review evaluates the main methodological contributions of artificial intelligence through machine learning. The methodology used to study the documents was content analysis; the basic terminology of the study corresponds to machine learning, artificial intelligence, and big data between the years 2017 and 2021. For this study, we selected 181 references, of which 120 are part of the literature review. The conceptual framework includes 12 categories, four groups, and eight subgroups. The study of data management using AI methodologies presents symmetry in the four machine learning groups: supervised learning, unsupervised learning, semi-supervised learning, and reinforced learning. Furthermore, the artificial intelligence methods with more symmetry in all groups are artificial neural networks, Support Vector Machines, K-means, and Bayesian Methods. Finally, five research avenues are presented to improve the prediction of machine learning. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.